The empowerment of rural women in Southern Africa: a case study of Driefontein, Kwazulu‐Natal - Catherine, Fiona Clare (University of the Free State, 2015)
This study explores the development challenges that rural women are facing in South Africa and the three Southern African Developing Countries (SADC) namely, Namibia, Swaziland and Zimbabwe. The researcher adopted a qualitative approach since this design was deemed most appropriate. The objectives of the study are to explore how women assess their situation in South Africa and the three SADC countries with regards to their socio‐economic realities. It is widely known that in many households, especially blacks, men leave home for urban areas in search of employment, leaving behind women to maintain the entire household on their own. Despite the significant role played by women, they are faced with problems such as those experienced by rural women in Sub‐Saharan countries. The study also endeavours to explore the most important development challenges of rural women in relation to education, health facilities, food insecurity, poverty, access to water and sanitation, the participation in the economy and politics, the HIV/AIDS pandemic and the impacts of climate change. Focus groups discussions and face to face interviews were conducted with information rich informants in the Driefontein rural area of KwaZulu Natal. Findings from the study show that Driefontein faces challenges which are interrelated. The findings further highlight that unemployment, failure on the part of local government to provide knowledge, training and monitoring of co‐operative ventures.
Dissertation (MGT (Governance and Political Transformation))--University of the Free State, 2015
Keywords: Rural women--South Africa--KwaZulu-Natal; Women in development--South Africa--KwaZulu Natal